DEFISIT APBN DAN PEMULIHAN EKONOMI PASCA KRISIS - Haryo Kuncoro (Signifikan: Jurnal Ilmu Ekonomi, 2013)
This research attempts to analyze the impact of deficit fiscal policy on the private expenditure in the case of Indonesia over the post crisis 2000-09 periods. The analysis is based on the goods market equilibrium. The approach is designed to analyze whether the government expenditure crowds out the private expenditure. In order to reach the objective of the study,this researchused the Linear Expenditure System (LES) and compared to the Almost Ideal Demand System (AIDS). The estimation result of quarterly data shows that the government expenditure did not crowd out the private expenditure. The crowding out only occurs partially especially on the private investment. However, the government expenditure totally remains stimulating the private expenditures. This, in turn, leads to increase the gross domestic product. Those results indicate that the expansionary fiscal policy effectively affects to the economic growth especially after economic crisis in 1997. Even, the income elasticity was much greater than that in the pre-crisis periodsDOI: 10.15408/sjie.v2i2.2422